2018
DOI: 10.1155/2018/8259280
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxysafflor Yellow A: A Promising Therapeutic Agent for a Broad Spectrum of Diseases

Abstract: Hydroxysafflor yellow A (HSYA) is one of the major bioactive and water-soluble compounds isolated from Carthami Flos, the flower of safflower (Carthamus tinctorius L.). As a natural pigment with favorable medical use, HSYA has gained extensive attention due to broad and effective pharmacological activities since first isolation in 1993. In clinic, the safflor yellow injection which mainly contains about 80% HSYA was approved by the China State Food and Drug Administration and used to treat cardiac diseases suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 101 publications
(107 reference statements)
0
45
0
1
Order By: Relevance
“…Hydroxysafflor yellow A, a flavonoid compound extracted from Carthamus tinctorius L., has received extensive attention and possesses broad pharmacological activities [ 90 ]. Zhang's research revealed that 5 mg/kg hydroxysafflor yellow A attenuated liver fibrosis by downregulating TGF- β 1, inhibiting phosphorylation of Smad4, and suppressing the ERK5 signaling pathways [ 91 , 92 ].…”
Section: Flavonoidsmentioning
confidence: 99%
“…Hydroxysafflor yellow A, a flavonoid compound extracted from Carthamus tinctorius L., has received extensive attention and possesses broad pharmacological activities [ 90 ]. Zhang's research revealed that 5 mg/kg hydroxysafflor yellow A attenuated liver fibrosis by downregulating TGF- β 1, inhibiting phosphorylation of Smad4, and suppressing the ERK5 signaling pathways [ 91 , 92 ].…”
Section: Flavonoidsmentioning
confidence: 99%
“…Due to its potency and minimal side effects, the clinical use of HSYA has continued to increase since 2000 (7). Previous studies have reported that safflower exerts antitumor effects (8), and it has been reported that HSYA prevented pulmonary metastasis in liver cancer cells (9), induced apoptosis in human gastric carcinoma cells (BGC-823 cells) (10) and inhibited the growth of transplanted BGC-823 tumors. Another study also reported that the effect of HSYA on tumor capillary angiogenesis may be one of the mechanisms underlying its antineoplastic effect (11).…”
Section: Introductionmentioning
confidence: 99%
“…Danshensu (DSS), salvianolic acid A (SAA), and salvianolic acid B (SAB) are the main hydrophilic components of Danshen (Figure 1) (Li et al, 2018c). Hydroxysafflor yellow A (HSYA) is a bioactive component of the dried flower of Honghua ( Figure 1) (Hui et al, 2018). Studies have shown that DSS, SAA, SAB, and HSYA have therapeutic effects on cardiovascular and CVDs, through anti-inflammatory, anti-oxidative activities, etc (Fan et al, 2017;Feng et al, 2017;Xu et al, 2017;Sun et al, 2018).…”
Section: Introductionmentioning
confidence: 99%